An efficient cable-type energy dissipation device for prevention of unseating of bridge spans. (August 2021) - Xing, Xinkui; Lin, Lanri; Qin, Heying
Abstract: During earthquakes, large relative displacements can be generated between different structural parts of a bridge. This can lead to collisions between the girder ends and the abutments and can even result in the girder unseating. A widely used prevention method adopts unseating prevention systems. The commonly cable-type unseating prevention device (C-CUPD) has low energy dissipation capacity and its cable fractures easily during strong earthquakes. In order to address these shortcomings, an energy dissipation cable-type unseating prevention device (E-CUPD) with an energy absorption tube is proposed in this study. The paper describes the basic structure and working mechanism of the device, and then investigates its energy absorption characteristics and limit performance, drawing upon theoretical analysis, numerical simulations, and testing of a scaled model. The influence of structural parameters and loading velocity on the energy absorption characteristics of the device are discussed, and the seismic responses of the bridge equipped with the device under different seismic input intensities are studied. The results show that the longer the device, the thicker the tube, and the larger the diameter, the better the energy absorption performance, while the larger the outer diameter, the lower the energy absorption performance. The axial expansion load of the energy absorption tube increases with an increase in the impact velocity. Before and after the characteristic velocity of 1 m/s, the sensitivity of load to velocity is weakened and the variation range decreases gradually. The integrity of the bridge structure equipped with the E-CUPD is improved and the seismic force is evenly distributed among piers with an acceptable value of spring displacement. The device can effectively reduce the relative displacement of the piers and beam subjected to different earthquakes and can absorb a large amount of seismic energy. With the increase in the seismic input intensity, the limiting effect of the E-CUPD becomes more prominent. At the higher seismic input intensities, the relative displacement of the pier and the beam can be reduced by nearly 30% compared to bridge without device. Compared to the C-CUPD, the E-CUPD can improve the limiting performance by about 15%.